2022
DOI: 10.2147/opth.s380629
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Ophthalmology Referral and Adherence in a Teleretinal Screening Program: Insights from a Federally Qualified Health Center

Abstract: Background: Early detection of ophthalmic conditions such as diabetic retinopathy (DR) and glaucoma is crucial to preventing vision loss. Previous studies have evaluated teleretinal screening programs for DR in well-insured populations. The purpose of this retrospective study was to evaluate a teleretinal screening program in a population of uninsured and underinsured patients seen in a Federally Qualified Health Center (FQHC). Methods: We conducted a retrospective chart review of patients (age ≥18) who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…10,12 Furthermore, compliance was shown to be more likely if a shorter follow-up time period was recommended, 11 the patient was prescribed eye drops, 13 or the patient received laser therapy. 10,13 Factors That Were Negatively Associated with Compliance Patient characteristics that were negatively associated with compliance included living alone, 16 smoking, 16 lacking a car, 16 Hispanic ethnicity, 23 or living farther from the hospital. 25…”
Section: Factors Positively Associated With Compliancementioning
confidence: 99%
“…10,12 Furthermore, compliance was shown to be more likely if a shorter follow-up time period was recommended, 11 the patient was prescribed eye drops, 13 or the patient received laser therapy. 10,13 Factors That Were Negatively Associated with Compliance Patient characteristics that were negatively associated with compliance included living alone, 16 smoking, 16 lacking a car, 16 Hispanic ethnicity, 23 or living farther from the hospital. 25…”
Section: Factors Positively Associated With Compliancementioning
confidence: 99%
“…A drawback of teleophthalmology screening using the store-and-forward model is the delay in diagnosis, which necessitates after-visit care coordination, increasing the likelihood of loss to followup. 92 In contrast, AI-based screening programs had increased adherence to follow-up recommendations in high-and low-resource countries alike 20 Topcon NW400 mtmDR Sensitivity, 88%; specificity, 90% EyeArt V2.2.0 (Eyenuk Inc, Woodland Hills, CA) 21 Canon CR-2 AF, Canon CR-2 Plus AF, and Topcon NW400 mtmDR and vtDR* mtmDR: sensitivity, 94-96%; specificity, 87-91%. † vtDR: sensitivity: 97%; specificity: 92% AEYE-DS (AEYE Health Inc, New York, NY) 22 Topcon NW400 mtmDR Sensitivity: 93%; specificity: 91% *Including severe non-proliferative diabetic retinopathy, proliferative diabetic retinopathy, and diabetic macular edema.…”
Section: Artificial Intelligence-based Image Analysismentioning
confidence: 99%
“…An important benefit of some AI-based screening systems is immediate feedback. A drawback of teleophthalmology screening using the store-and-forward model is the delay in diagnosis, which necessitates after-visit care coordination, increasing the likelihood of loss to follow-up 92 . In contrast, AI-based screening programs had increased adherence to follow-up recommendations in high- and low-resource countries alike due to immediate feedback on referral status 93,94 .…”
Section: Teleophthalmology Approaches To Diabetic Retinopathy Screeningmentioning
confidence: 99%
“…In the underserved population sampled in this study, more than 60% of the 2050 diabetic patients reported that their last eye examination had been conducted more than 3 years previously 12 . This lack of adherence is significantly higher among underserved individuals with low-income levels and minority ethnic backgrounds, such as African Americans and non-Hispanic Caucasians 20–22 . Barriers preventing routine eye examinations present a major hurdle to the timely detection and treatment of diabetic retinopathy.…”
mentioning
confidence: 93%
“…12 This lack of adherence is significantly higher among underserved individuals with lowincome levels and minority ethnic backgrounds, such as African Americans and non-Hispanic Caucasians. [20][21][22] Barriers preventing routine eye examinations present a major hurdle to the timely detection and treatment of diabetic retinopathy.…”
mentioning
confidence: 99%